IMPROVEMENT OF SHEEP OOCYTE COMPETENCE IN VITRO THROUGH GLUTATHIONE ADDITION - Yusmala, Mitha; Supriatna, Iman; Setiadi, Mohamad Agus (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Oocyte competence is a primary factor for the success of embryo production in vitro. This research aims to determine the effect of supplementation glutathione in sheep oocytes’ maturation and fertilization rates in vitro. In the first research, maturation oocytes were conducted in a medium supplemented with GSH at graded doses for 24 hours. In the second research, 1.0 mM GSH (the best dose from research I) was supplemented in the maturation medium, fertilization medium, and their combination for 14 hours. The higher oocyte maturation rates were significant (P < 0.05) in the GSH supplementation of 1.0 mM (87.00%). Furthermore, supplementation of GSH on the maturation medium resulted in a higher normal fertilization rate (56.43%) than in other groups. It is concluded that GSH supplementation on the maturation medium is more effective in increasing the competence of sheep oocytes to be mature and results in improved fertilization rates.